Adhesion promotion by ESI deposition of thin polymer layers onto carbon fibers. Issue 4 (6th October 2015) - Friedrich, Jörg F.; Wettmarshausen, Sascha; Altmann, Korinna; Hidde, Gundula
Abstract : Thin coatings of high-molecular weight poly(acrylic acid) (PAA) and poly(hydroxyethyl methacrylate) were deposited onto carbon fibers by means of atmospheric electrospray ionization (ESI) as adhesion promoters in carbon fiber–epoxy resin composites. The carbon fibers were completely wrapped by pinhole-free polymer coatings in the upper 10 plies of a carbon fiber roving (corresponding to 50–100 µm) as verified with scanning electron microscopy ('electrophoretic effect'). The polymer films have either a granular or a smooth structure depending on the absence or presence of residual solvent in the deposit. The ESI-deposited PAA films did not show any changes in composition and structure referenced to commercial PAA as analyzed by X-ray photoelectron spectroscopy and matrix-assisted laser desorption ionization time-of-flight mass spectrometry. Single fiber pull-out tests demonstrated significantly increased adhesion of coated carbon fibers to epoxy resin. It is assumed that chemical bonds between carbon fiber-PAA and epoxy resin contribute significantly to the improved interactions.